The Importance of Accurate Host Species Identification in the Framework of Rabies Surveillance, Control and Elimination - De Benedictis, Paola; Leopardi, Stefania; Markotter, Wanda; Velasco-Villa, Andres (Viruses, 2022)
Accurate host identification is paramount to understand disease epidemiology and to apply appropriate control measures. This is especially important for multi-host pathogens such as the rabies virus, a major and almost invariably fatal zoonosis that has mobilized unanimous engagement at an international level towards the final goal of zero human deaths due to canine rabies. Currently, diagnostic laboratories implement a standardized identification using taxonomic keys. However, this method is challenged by high and undiscovered biodiversity, decomposition of carcasses and subjective misevaluation, as has been attested to by findings from a cohort of 242 archived specimens collected across Sub-Saharan Africa and submitted for rabies diagnosis. We applied two simple and cheap methods targeting the Cytochrome b and Cytochrome c oxidase subunit I to confirm the initial classification. We therefore suggest prioritizing a standardized protocol that includes, as a first step, the implementation of taxonomic keys at a family or subfamily level, followed by the molecular characterization of the host species.